A descriptive analysis of Ilongo suffixes - Sobrepena, Lucila P. 1925-; Manza, Fe (Quezon City College of Education, University of the Philippines Diliman, 1966)
This is a descriptive analysis of Ilongo suffixes. Suffixes in Ilongo are bound forms which may be added to a root or a stem to form a new class of words. They may be derivational or inflectional in nature.
Thesis (Master of Arts in Teaching English as Second Language)--University of the Philippines Diliman
Keywords: Ilongo dialect -- Suffixes and prefixes